2007
DOI: 10.1111/j.1524-475x.2007.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term bone marrow culture and its clinical potential in chronic wound healing

Abstract: Bone marrow-derived cells have long been regarded to play a crucial role in the homeostasis of skin. We have previously described the clinical benefit of directly applying autologous bone marrow aspirate and cultured bone marrow cells to recalcitrant chronic skin wounds. The initial response to treatment appears to be vascular in nature with the formation of new blood vessels. The difficulty in consistently growing adequate numbers of cells for delivery to patients was, however, a limiting factor. Here, in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 45 publications
2
38
1
Order By: Relevance
“…Previous work in our laboratory has demonstrated that bone marrow-derived cells play an important role in cutaneous wound healing and that direct application of bone marrow-derived cells to patients with chronic nonhealing wounds leads to wound closure and dermal rebuilding [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in our laboratory has demonstrated that bone marrow-derived cells play an important role in cutaneous wound healing and that direct application of bone marrow-derived cells to patients with chronic nonhealing wounds leads to wound closure and dermal rebuilding [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, unavoidable vascular damage is often created during actinic, cytostatic or surgical therapy of tumors, and thus, development of gentle and specific tumoricidal therapies like targeted photodynamic approaches may help spare the normal tissue of oncology patients (134). Although in some other oncological strategies there has been a considerable effort made toward inhibition and/or destruction of blood vessels to devitalize tumor tissues (135), the opposite effort is usually exercised in tissue engineering and wound healing research (136,137) to keep regenerating or engineered tissues alive and functional. Three major areas of vessel engineering can be distinguished: i) reconstruction of large vessels using transplants and prostheses, ii) creation or induction of vessels in bioengineered constructs (i.e., imitation of embryonic vasculogenesis), and iii) enhancement of vessel invasion into the engineered material from the neighboring tissues (angiogenesis).…”
Section: Organ Level: Integration Of All Memory Mechanismsmentioning
confidence: 99%
“…More importantly, these beneficial effects seemed to be mediated through paracrine effects [44]. MSCs can attract macrophages, VSMCs and other types of cells to the wound site to release a variety of angiogenic factors involved in tissue repair [45, 46]. MSCs stimulate the release of paracrine factors, thus playing a role in the paracrine mechanism, thereby inducing the function of endogenous tissue cells [47, 48].…”
Section: Discussionmentioning
confidence: 99%